PENDAMPINGAN PENYUSUNAN STANDAR OPERASIONAL PROSEDUR (SOP) SIMPAN PINJAM UNTUK MENINGKATKAN PROFESIONALISME PADA KSU PUSPA SARI SEDANA MELALUI PROGRAM MBKM - Ingke Nurahmaniah; Retna Cahyaningtyas, Susi; Husnaini, Wahidatul; Erlina Sasanti, Elin (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2025)
The Independent Learning Independent Campus Internship Program (MBKM) provides contextual learning spaces for students through direct involvement in partner organizations. This activity was carried out at the Puspa Sari Sedana Business Savings Cooperative (KSU), West Nusa Tenggara, which is the main operation in the field of member financing services. KSU Puspa Sari Sedana has been established since 2007. Even though it has been established for 18 years, this cooperative still operates very simply and the main focus of the cooperative's activities is currently fixed on savings and loan activities and most of the managerial and recording processes that occur in it are still carried out manually and the cooperative does not have a recorded SOP that can be used. Through the MBKM facilitation activities, the team developed savings and loan SOPs based on the results of participatory observations, interviews, and document studies conducted within the cooperative. With the establishment of documented savings and loan SOPs, it is expected that there will be clear guidelines for operational implementation at KSU Puspa Sari Sedana, enabling processes to become more systematic and well-structured, reducing recording errors, and enhancing transparency and accountability in the cooperative’s management.